Chapel Hill Expert Survey trend file, 1999–2019. (February 2022) - Jolly, Seth; Bakker, Ryan; Hooghe, Liesbet; Marks, Gary; Polk, Jonathan; Rovny, Jan; Steenbergen, Marco; Vachudova, Milada Anna
Abstract: Research on party competition and political representation relies on valid cross-national measures of party positions. This research note reports on the 1999–2019 Chapel Hill expert survey (CHES), which contains measures of national party positioning on European integration, ideology, and several European Union (EU) and non-EU policies for six waves of the survey, from 1999 to 2019. The trend file provides party position measures for all 28 EU countries and 1196 party-year observations. In this article, we analyze the evolving party positions on European integration from 1999 to 2019, with a particular focus on how EU positions are related to economic left-right and the Green/Alternative/Libertarian-Traditional/Authoritarian/Nationalist dimension (GAL-TAN). The dataset is publicly available on the CHES website.